2014
DOI: 10.1590/s1806-37132014000500006
|View full text |Cite
|
Sign up to set email alerts
|

Barriers associated with reduced physical activity in COPD patients

Abstract: OBJECTIVE: To evaluate the ability of COPD patients to perform activities of daily living (ADL); to identify barriers that prevent these individuals from performing ADL; and to correlate those barriers with dyspnea severity, six-minute walk test (6MWT), and an ADL limitation score. METHODS: In COPD patients and healthy, age-matched controls, the number of steps, the distance walked, and walking time were recorded with a triaxial accelerometer, for seven consecutive days. A questionnaire regarding perceived bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Whereas almost all included smokers (n ϭ 31) had a sedentary life style, compared with the non-COPD group, the COPD group had statistically significantly lower physical activity scores (see Table 1). The above result was similar to that reported by Amorim et al, 57 where the COPD group (n ϭ 40), when compared with the non-COPD group (n ϭ 40), had a significantly greater limitation in activities of daily living 58 (33 Ϯ 11 vs 21 Ϯ 2, respectively).…”
Section: Evaluation Of Handicapsupporting
confidence: 91%
“…Whereas almost all included smokers (n ϭ 31) had a sedentary life style, compared with the non-COPD group, the COPD group had statistically significantly lower physical activity scores (see Table 1). The above result was similar to that reported by Amorim et al, 57 where the COPD group (n ϭ 40), when compared with the non-COPD group (n ϭ 40), had a significantly greater limitation in activities of daily living 58 (33 Ϯ 11 vs 21 Ϯ 2, respectively).…”
Section: Evaluation Of Handicapsupporting
confidence: 91%
“…While recent reviews have investigated the reasons for poor adherence or dropout of PR, this has not until now been extended to include participation in PA as part of daily life 29,30. One study that did focus on the barriers specific to activities of daily living was a cross-sectional study from Brazil 31. The study demonstrated an association between social influences, lack of infrastructure, and lack of willpower and lower PA among people with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The standardised CPET plays an important role in social and occupational medicine, when an impairment of the cardiopulmonary capacity needs to be quantified. The 6-minute walk reflects limitations expected in activities of daily life (ADL) (17). A significant relationship between walking distance and FEV1 and FVC was reported (17).…”
Section: Discussionmentioning
confidence: 99%